2007
DOI: 10.1080/09585190601102547
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management and performance in a developing country: the case of Eritrea

Abstract: This study investigates the relationship between human resource management (HRM) practices and organizational performance. Results based on a sample of 82 organizations from private and public sectors in Eritrea indicate that some of the practices have a significant impact on employee turnover, absenteeism, grievances and productivity. While compensation was the only independent variable found to be statistically significant in affecting grievances, employee selection had no effect across all performance measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
1
25
0
3
Order By: Relevance
“…From 2003 onward, seven studies have been found that measure the impact of training/HRM practices on HR outcomes such as employee involvement, turnover, employee satisfaction, and commitment (Aragón et al 2003;Lee and Bruvold 2003;Paul and Anantharaman 2003;Wright et al 2003;Edgar and Geare 2005;Garcia 2005;Chebregiorgis and Karsten 2007). Two of these studies (Paul and Anantharaman 2003;Wright et al 2003), attempt to build on the casual inferences that can be drawn between HRM practices (including training) and organizational performance; they seek to establish casual models to prove the value of HRM practices (among them training) at the organizational level.…”
Section: Performance: Content and Measuresmentioning
confidence: 98%
“…From 2003 onward, seven studies have been found that measure the impact of training/HRM practices on HR outcomes such as employee involvement, turnover, employee satisfaction, and commitment (Aragón et al 2003;Lee and Bruvold 2003;Paul and Anantharaman 2003;Wright et al 2003;Edgar and Geare 2005;Garcia 2005;Chebregiorgis and Karsten 2007). Two of these studies (Paul and Anantharaman 2003;Wright et al 2003), attempt to build on the casual inferences that can be drawn between HRM practices (including training) and organizational performance; they seek to establish casual models to prove the value of HRM practices (among them training) at the organizational level.…”
Section: Performance: Content and Measuresmentioning
confidence: 98%
“…Description of the approach Studies Approach 1 Single informant: a single informant with a different position in each unit of analysis provides answers to all questions in the questionnaire, and no differentiation is made between them in the analysis Audea, Teo and Crawford (2005), Chen and Huang (2009), Delaney and Huselid (1996), De Winne and Sels (2010), Fey and Björkman (2001), Fey, Björkman and Pavlovskaya (2000), Gerhart and Milkovich (1990), Ghebregiorgis and Karsten (2007), Gibson et al (2007), Guest et al (2003), Guthrie (2000Guthrie ( , 2001, Harel and Tzafrir (1999), Iverson and Zatzick (2011), Kalleberg and Moody (1994), Kepes, Delery and Gupta (2009), Kintana, Alonso and Olaverri (2006), Lee and Chee (1996), Li (2003), Litz and Stewart (2000), McClean andCollins (2011), Miah andBird (2007), Minbaeva et al (2003), , Perry-Smith and Blum (2000), Rodwell and Teo (2008), Shih, Chiang and Hsu (2006), Skaggs and Youndt (2004), Tzafrir (2005aa, 2005bb), Vlachos (2008), Wood, Holman and Stride (2006) (N = 32) Approach 2…”
Section: Research Approachmentioning
confidence: 99%
“…In the case of OSPs, the scarcity of skilled IT professionals has been identified as a major constraint for their growth (Farrell and Grant ; Schuler, Jackson and Tarique ), and the availability of skilled human resources has been identified as a key factor among firms in advanced industrialised countries when deciding on an offshore outsourcing location (Graf and Mudambi ; Lewin, Massini and Peeters ). As the ‘global race for talent’ (Lewin, Massini and Peeters ) and ‘the war for talent’ (McKinsey ) intensify due to the shortage of skilled IT professionals, the performance of technology and knowledge‐intensive, people‐based firms such as OSPs is being increasingly linked to the effectiveness with which they manage their talent pool (Ghebregiorgis and Karsten ; Guest ; Harris and Ogbonna ; Kaya ). A firm's talent management embodies its deliberate activities to optimally recruit, retain, train, develop and deploy highly skilled people in strategically identified positions in the organisation.…”
Section: Theoretical Considerations and Hypothesesmentioning
confidence: 99%